PERHITUNGAN WAKTU BAKU DENGAN BERBAGAI VARIASI PRODUK DI PT X - Susanti, Eni; Palit, Herri Christian; Aysia, Debora Anne Anne Yang (Jurnal Titra, 2015)
Abstract: PT X is karoseri companies that produce box of trucks in general and particular design (Customized design). There are many delays in the fulfillment of customer order. This is caused by a high variety type and size of the vehicles and the company didnât know time period that is needed to make a product with certain specifications. The purpose of this research is to find the time that is needed to make single product with a specific car size and type (especially for a new type that hasnât been requested before). Aluminium box type can be classified in 11 different type of cars. Based on 11 types of car there are 6 work process which contain of 342 work process elements.Â The data collection is perfomed using a stopwatch time study. As a result, the working element can be divided into 2 kind of time calculation. They are work element which is based on the quntity of the product component and work element which is based on the dimension of the product component.